2017
DOI: 10.1016/j.stemcr.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Generation of Vascular Wall-Resident Multipotent Stem Cells of Mesenchymal Nature from Murine Induced Pluripotent Stem Cells

Abstract: SummaryThe vascular wall (VW) serves as a niche for mesenchymal stem cells (MSCs). In general, tissue-specific stem cells differentiate mainly to the tissue type from which they derive, indicating that there is a certain code or priming within the cells as determined by the tissue of origin. Here we report the in vitro generation of VW-typical MSCs from induced pluripotent stem cells (iPSCs), based on a VW-MSC-specific gene code. Using a lentiviral vector expressing the so-called Yamanaka factors, we reprogram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 51 publications
2
38
0
Order By: Relevance
“…Importantly, the famous and well-known identity switch of whole body parts, the homeotic transformation, which is induced by altered Hox expression 9,10 , shows that Hox TFs have comparable functions in all lineages during development and indicates that they control the development of different lineages in a highly specific manner. The latter conclusion is supported by recent experiments showing that mesoderm-derived vascular wall mesenchymal stem cells (VW-MSCs) can be generated in vitro from induced pluripotent stem cells (iPSCs) simply by inducing the expression of a mixture of Hox genes that are selectively expressed in adult VM-MSCs 11 . However, while this study showed that Hox genes alone are sufficient to induce the generation of one specific cell type of one lineage in vitro, it left the questions open whether this is also the case in vivo, and how Hox TFs unambiguously select among the many possible transcriptional programs only one, which drives a cell or a whole lineage into one specific direction.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…Importantly, the famous and well-known identity switch of whole body parts, the homeotic transformation, which is induced by altered Hox expression 9,10 , shows that Hox TFs have comparable functions in all lineages during development and indicates that they control the development of different lineages in a highly specific manner. The latter conclusion is supported by recent experiments showing that mesoderm-derived vascular wall mesenchymal stem cells (VW-MSCs) can be generated in vitro from induced pluripotent stem cells (iPSCs) simply by inducing the expression of a mixture of Hox genes that are selectively expressed in adult VM-MSCs 11 . However, while this study showed that Hox genes alone are sufficient to induce the generation of one specific cell type of one lineage in vitro, it left the questions open whether this is also the case in vivo, and how Hox TFs unambiguously select among the many possible transcriptional programs only one, which drives a cell or a whole lineage into one specific direction.…”
Section: Introductionmentioning
confidence: 88%
“…1). Pearson correlation coefficient analysis revealed that the transcriptome of the mesodermal lineage was clearly distinct from the neuronal one at both time points (r=0.72 for stages [10][11][12][13] ; r=0.53 for stages [14][15][16][17] ) ( Fig. 1F, Supplementary Fig.…”
Section: Drosophila Embryonic Mesodermal and Neuronal Lineagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Mesenchymal stem cells (MSCs) have been well characterized and can be isolated from various tissues, such as bone marrow, 3 adipose, 4 umbilical cord, 5 placenta, 6 and circulatory vessel walls. 7 Because of a number of functional advantages, including self-proliferation, multi-differentiation, injury foci chemotaxis, anti-inflammation, and immunomodulation, this cell population has become a focus of research. 8 MSC-based therapies have been successfully used to repair tissue and several organs, including the lungs.…”
Section: Introductionmentioning
confidence: 99%